Examination of physical fitness parameters of trainable individuals with intellectual disability - Bilal Karakoç (Revista on line de Política e Gestão Educacional)
This study was conducted to compare the physical fitness values of children with intellectual disability aged 13-18 according to some parameters within the scope of the physical activities project. The study group consists of 12 trainable intellectual disabled individuals. In the study, pre-test and post-test values were taken for the physical fitness test scores of the trainable disabled individuals. The first weight averages of the subjects participating in the study were 69.58 ± 8.8, the last measurement results were 70.08 ± 10.1, the Biceps measurement averages were 7.42 ± 2.9 in the first measurement, the average of the post-test measurement results were 10.58 ± 6.4, the Triceps averages of the first measurement results were 12.75 ± 5.4. As a result of the study, it can be said that the participation of trainable intellectual disabled young people in sports activities has a positive effect on their physical fitness.